IMPLEMENTASI MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 035 SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Marliza Marliza; Eddy Noviana; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low learning outcomes IPA third grade students of SD Negeri 035 Sekeladi with rata average grade 71.68 with a minimum completeness criteria (KKM) of science learning was 75 of total 29 students only 12 students who reach KKM and 17 students did not reach KKM. Penelitian The application is titled quantum teaching model for improving student learning outcomes science class III SD Negeri 035 Sekeladi Tanah Putih Rokan Hilir. This research aims to improve learning outcomes of science learning third grade students of SD Negeri 035 Sekeladi academic year 2014/2015 with the adoption of quatum teaching model. This research was conducted by 2 cycles refers to the student results, activities student and teacher activity. At the first meeting activity first cycle teacher with a percentage increase of 66.66%, second meeting to be 75.00%. In the first meeting of the second cycle increased again to 83.33% after the second meeting increased to 91.66% by Both very category. Activities students in first cycle first meetings with the percentage of 62.50% has increased to a second meeting be 70.83%. In the first meeting of the second cycle increased again became 79,16% and then increased again to a second meeting be 87.50%. Model quatum teaching in the learning process can improve student learning outcomes of science learning than the average score of 71.68 into 74.82 basis in the first cycle of the next increased by 3.14% and then increased from 74.82 in the first cycle to 83.10 with a large increase of 8.28%. Based on these results it can be concluded that the adoption of the model quantum teaching can improve learning outcomes of science learning grade III SD Negeri 035 Sekeladi Tanah Putih Rokan Hilir.Keywords: quantum teaching learning model